Penerapan Kahoot berbasis Games-Based Learning pada Mata Pelajaran Dasar Ketenagalistrikan - Zulina, Putri; Mukhaiyar, Riki (Jurnal Pendidikan Teknik Elektro, 2025)
This study aims to determine the application of games-based learning assisted by Kahoot in improving student learning outcomes in basic electricity subjects at SMK Muhammadiyah 1 Padang. Conventional learning methods that tend to be monotonous and less interactive are one of the causes of low motivation and student learning outcomes. This study uses an experimental method with a one-group pretest-posttest design. The research instrument is a learning outcome test consisting of a pretest and a posttest. The data analysis techniques used in this study are the N-Gain test, effect size, and completeness of learning outcomes. The results of the study show that the application of games-based learning assisted by Kahoot significantly improves student learning outcomes. The average score of the posttest students increased compared to the pretest, with the results of the N-Gain test showing a moderate improvement category and an effect size in the large category. Student learning completeness was also achieved with a percentage of 86%. Thus, Kahoot is effective in increasing student motivation and learning outcomes in this subject.